1966
DOI: 10.1149/1.2423886
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Properties of Thin Films of Zn[sub x]Cd[sub (1−x)]S

Abstract: Films of the solid solution system ZnxCdfalse(1−xfalse)S have been produced by simultaneous evaporation from two separately controlled sources onto a single substrate. Films of uniform composition were made covering the full range from 0 to 100% normalZnS concentration, and the dependence of energy gap, crystal habit, and lattice parameter on composition was investigated. Optical transmission edge measurements yielded a nearly linear dependence of gap width on composition between the values of 2.35 ev for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

1978
1978
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 1 publication
0
12
0
3
Order By: Relevance
“…There is a considerable disagreement in the literature concerning the variation of the lattice constants with composition (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The obtained phases and the variation of the lattice constants showed a marked and complicated dependence on the growth conditions.…”
Section: Fig 2 Lattice Constants A~r and C • And Mean Grain Size Dmentioning
confidence: 99%
“…There is a considerable disagreement in the literature concerning the variation of the lattice constants with composition (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The obtained phases and the variation of the lattice constants showed a marked and complicated dependence on the growth conditions.…”
Section: Fig 2 Lattice Constants A~r and C • And Mean Grain Size Dmentioning
confidence: 99%
“…] centrations : y = 0; 0,095 et 0,17. Les valeurs de Eg obtenues sont représentées sur la figure 10 où on a porté également les résultats des travaux effectués sur des couches similaires préparées par pulvérisation avec air [5,15,16] et par évaporation thermique [8]. Dans la région de composition considérées (0 y 0,2) les valeurs de Eg des couches fabriquées par les trois méthodes suivent la même loi de variation en fonction de la concentration en zinc, ces valeurs sont assez voisines pour une concentration déterminée (Tableau II), l'écart relativement important pour y = 0 est réduit pour les plus grandes concentrations.…”
Section: Couchesunclassified
“…8 Nos résultats : Pulvérisation chimique sans air (T, = 420 °C, 1 pm 5 e 4 um) ; x Réf. [8] : évaporation thermique (p = 3 x 10-6 torr, e = 0,5 pm) échantillon recuit à 450 °C pendant 15 min ; 0 Réf. [5] : pulvérisation chimique avec air (T. = 450 °C, e = 2um); A Ré£ [15] : pulvérisation chimique avec air (0,5 pm e 10 pm); 1 Réf.…”
Section: Couchesunclassified
See 1 more Smart Citation
“…Tohge et al [2] performed the sulfuration of Cd and Zn introducing in the sol a methanolic solution of thiourea. Kane et al [3] have shown that a complete solid solution exists between ZnS and CdS in thin films. Barret et al [4] indicate that Zn forms a substitutional solid solution with CdS, shifting the band gap to higher energies.…”
Section: Introductionmentioning
confidence: 99%